Effects of Anaerobically Digested Slurry on Meloidogyne incognita and Pratylenchus penetrans in Tomato and Radish Production - Yu Yu Min; Koki Toyota; Erika Sato; Atsushi Takada (Applied and Environmental Soil Science)
Since effective disposable way of anaerobically digested biogas slurry is expected, ADS was applied to soil to evaluate its effects on nematode damage. Damage index of tomato by root-knot nematode was significantly (𝑃<.05) lower and the growth better in pots applied with ADS (100 and 200 mg NH+4-N kg−1) than that in those with chemical fertilizer and control (no ADS). ADS was applied into radish cultivated fields infested with the root-lesion nematode: a single (100 kg NH+4-N ha−1) in 2007 and 2008 and multiple applications (25, 50, 25 kg NH+4-N ha−1 soil) in 2009. Damage to radish was 30% and 50% lower in ADS-treated fields than that in the control in 2007 and 2009, respectively, although not in 2008. These results suggest that application of ADS to fields might be feasible for mitigating nematode damage, but the rate and timing should be considered further for the best application way.